Intensive behavioural interventions based on applied behaviour analysis for young children with autism: An international collaborative individual participant data meta-analysis. (May 2021) - Rodgers, Mark; Simmonds, Mark; Marshall, David; Hodgson, Robert; Stewart, Lesley A; Rai, Dheeraj; Wright, Kath; Ben-Itzchak, Esther; Eikeseth, Svein; Eldevik, Sigmund; Kovshoff, Hanna; Magiati, Iliana; et al.
This individual participant data meta-analysis is the most intensive possible evaluation of the effectiveness of early intensive applied behaviour analysis–based interventions for pre-school autistic children compared with treatment as usual/eclectic interventions. Data from 491 participants (originally collected in 10 studies) were included. Children receiving early intensive applied behaviour analysis–based interventions improved more on the Vineland adaptive behaviour scale (MD = 7.00; 95% confidence interval = 1.95–12.06) and cognitive ability (intelligence quotient) (MD = 14.13; 95% confidence interval = 9.16–19.10) relative to comparators at 2 years; though effects varied considerably across studies. Evidence for other outcomes was inconclusive due to insufficient evidence and there were few data on longer-term effects. All studies were at risk of bias across several domains, often due to the lack of randomisation or blinding of outcome assessors. Given the emerging evidence of modest, albeit short term, effects of a range of pre-school autism interventions and the limitations of the quality of evaluation studies to date, future research should investigate which supports and interventions are most effective for children and families prioritising outcomes measures that are meaningful for the autism community and longer-term follow-up. Further systematic reviews of the existing evidence are unlikely to add to the findings presented here. Lay abstract: Early intensive applied behaviour analysis–based interventions are designed to support young autistic children's learning and development. Unfortunately, the available evidence about the effectiveness of these interventions remains unclear. Several reviews have focused on the published findings rather than contacting the authors to collect and analyse data about the individual participants in the original studies. Also, most of the studies were carried out by groups involved in delivering the interventions leading to the potential bias in interpreting the results. Our research team (supported by an international advisory group) carried out an independent individual patient data review by collecting the original participant data from the authors of the studies, to examine the effectiveness of these interventions. The results suggested that early intensive applied behaviour analysis–based interventions might lead to some changes in children's cognitive ability (intelligence quotient) and everyday life skills after 2 years, compared with standard treatments. However, all the studies had problems with the way they were designed. Also, few of the studies looked at outcomes that have been described as most important to autistic people or followed children beyond 2 years. We think that further systematic reviews of the existing evidence are unlikely to add to the findings of our review. Furthermore, we recommend that future research should investigate which types of supports and interventions are most effective for children and families, prioritising outcomes measures that are meaningful for the autism community and include, wherever possible, longer-term follow-up.